Unequal shares: wealth in Britain - Atkinson, A. B. (London: Allen Lane, 1972)
The book aims at pro viding evidence about the distribution of wealth in Britain and to examine the consequences of reforms. The book is divided into four parts. Part 1 is concerned with the distribution of wealth in Britain and the causes of inequality. Parts 2 &3 deal with the various measures that have been proposed with the objective of securing greater equality. Part 4 attempts to summarize the conclusion of Parts 2 & 3.
Bibliography: p. 264-269.
osa; 06/11/2017
Loans
Keywords: Wealth; Taxation